Sol–gel-derived bioactive glass nanoparticle-incorporated glass ionomer cement with or without chitosan for enhanced mechanical and biomineralization properties. Issue 7 (July 2017) - Kim, Dong-Ae; Lee, Jung-Hwan; Jun, Soo-Kyung; Kim, Hae-Won; Eltohamy, Mohamed; Lee, Hae-Hyoung
Graphical abstract: Highlights: Sol–gel derived bioactive glass nanoparticles (BGNs) were successfully fabricated with ∼42 nm in diameter with bioactivity. The incorporation of BGNs into glass ionomer cement (GIC) led to increased mechanical and bioactive properties. The incorporation of BGNs into GIC led to increased biomineralization with human dental pulp stem cells without cytotoxicity. The developed BGNs-incorporated GIC is considered as a promising restorative dental material. Abstract: Objective: This study investigated the mechanical and in vitro biological properties (in immortalized human dental pulp stem cells (ihDPSCs)) of bioactive glass nanoparticle (BGN)-incorporated glass ionomer cement (GIC) with or without chitosan as a binder. Methods: After the BGNs were synthesized and characterized, three experimental GICs and a control (conventional GIC) that differed in the additive incorporated into a commercial GIC liquid (Hy-bond, Shofu, Japan) were produced: BG5 (5 wt% of BGNs), CL0.5 (0.5 wt% of chitosan), and BG5 + CL0.5 (5 wt% of BGNs and 0.5 wt% of chitosan). After the net setting time was determined, weight change and bioactivity were analyzed in simulated body fluid (SBF) at 37 °C. Mechanical properties (compressive strength, diametral tensile strength, flexural strength and modulus) were measured according to the incubation time (up to 28 days) in SBF. Cytotoxicity (1 day) and biomineralization (14 days), assessed by alizarin red staining, were investigated using an extract from GIC and ihDPSCs. Data were analyzed using one-way analysis of variance (ANOVA) followed by Tukey's post hoc test; p < 0.05. Results: BGNs were sol–gel synthesized to be approximately 42 nm in diameter with a spherical morphology and amorphous structure. After the bioactivity and suspension ability of the BGNs were confirmed, all the experimental GIC groups had setting times of less than 6 min and approximately 1% weight loss after 28 days of incubation. In addition, BGNs incorporated into GIC (BG5 and BG5 + CL0.5) exhibited surface bioactivity. The mechanical properties were increased in the BGN-incorporated GICs compared to those in the control (p < 0.05). Without cytotoxicity, the biomineralization capacity was ranked in the order BG5, BG5 + CL0.5, control, and CL0.5 (p < 0.05). Significance: BGN-incorporated GIC showed enhanced mechanical properties such as compressive, diametral tensile and flexural strength as well as in vitro biomineralization properties in ihDPSCs without cytotoxicity. Therefore, the developed BGN-incorporated GIC is a promising restorative dental material, although further in vivo investigation is needed before clinical application.